Online Couple Therapy: Reflections From Reluctant Converts - Nic Beets; Verity Thom (Psychotherapy and Counselling Journal of Australia)
We are two seasoned couple therapists reflecting on our experience of being abruptly forced by the COVID-19 crises to shift from in-person to online couple therapy. In this article, we offer our subjective view of the relative merits of the two formats, with an emphasis on the unexpected benefits to both client and therapist of doing couple therapy online. We also offer some suggestions for making couple therapy work well online, based on our clinical experience.